2018
DOI: 10.1111/jav.01784
|View full text |Cite
|
Sign up to set email alerts
|

Causes of seasonal decline in reproduction of the cooperatively‐breeding acorn woodpecker

Abstract: Clutch size and reproductive success decline seasonally in a wide range of temperate avian taxa. Two competing hypotheses have been proposed to explain such declines: the ‘timing’ hypothesis, which states that conditions affecting reproduction decline intrinsically with date, and the ‘quality’ hypothesis, which proposes that high‐quality individuals or individuals in high‐quality situations breed earlier. We contrasted the relative importance of these two hypotheses using a long‐term dataset of the cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Consistent with other studies (Koenig & Walters, 2018;Musselman, 1935;White & Woolfenden, 1973), a post hoc analysis revealed that within each breeding season, hatchability declined from start to end of the season (0.92 ± 0.004 to 0.89 ± 0.013, p < .001). Our best hatchability model contained variability in precipitation in the nonbreeding season (Table 3), with this variable having an inverse relationship with hatchability.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other studies (Koenig & Walters, 2018;Musselman, 1935;White & Woolfenden, 1973), a post hoc analysis revealed that within each breeding season, hatchability declined from start to end of the season (0.92 ± 0.004 to 0.89 ± 0.013, p < .001). Our best hatchability model contained variability in precipitation in the nonbreeding season (Table 3), with this variable having an inverse relationship with hatchability.…”
Section: Discussionsupporting
confidence: 89%
“…One prominent explanation for the occurrence of cooperative breeding in birds in variable environments is that it represents a 'bethedging' strategy [38], whereby breeding individuals share the costs of reproduction with helpers and are thus able to reduce interannual variation in reproductive success in response to unpredictable rainfall and food availability [9]. This implies that cooperation might buffer breeding attempts from failure during adverse environmental conditions [13,41].…”
Section: And Van Dementioning
confidence: 99%
“…In some species, lower‐quality parents have smaller broods (Sydeman et al. 1991) and tend to nest later in the breeding season (Koenig and Walters 2018). Thus, higher provisioning rates earlier in the season could be due to the presence of a greater number of nestlings.…”
Section: Discussionmentioning
confidence: 99%